Istikhdām Lu‘bah Thu‘bān wa Sullam li Tarqiyyati Raghbati Ta‘allumi al-Qiraati wa Injāzihi fi al-Madrasati al-Mutawāsiṭati - Umi Habibah; Dwi Mawanti; Achmad Zuhruddin (Alsina : Journal of Arabic Studies, 2020)
This research aims to calculate the pupils’ desire and achievement in learning to read among those who use the snake and ladder game and those who do not use it in Madrasah Tsanawiyah Negeri 1 Kudus for the academic year 2019-2020. Based on the number of students in the school, we preferred two classes, the eighth - a experimental group, and the eighth - b as a control group for the purpose of experimental research. The methods used to collect data are observation, interview, documentation, questionnaire, and testing. The results of this research indicated that teaching reading skill using this game is better than without it, so that the average grade for the experimental semester is 85.69 and the average grade for the control class is 79.72. To test the hypothesis, I got t calculation = 5,209 compared to -table t = 1,9944. The mean is higher in the experimental group than in the control group. This means that there is a big difference in learning to read after and without using this game. As for the result of the questionnaire, it indicated that the desire to read using this game is 55% to 92.75%, an increase of 37.75%, and the researcher is sure that the result is high between the pre and post test. It can be concluded that using the game Ular Tangga is suitable for promoting students' desire and achievement in learning to read.